Hubungan Asupan Vitamin E Dan Kolesterol Dengan Kadar High Density Lipoprotein (HDL) Pada Pasien Penyakit Jantung Koroner Di Ruang Rawat Inap RSUD Dr. Moewardi - KURNIASARI, Lutfiana Dewi; , Ririn Yuliati S.Si.T., M.Si; , Setyaningrum Rahmawaty, A., M.Kes., Ph.D (2015)
Background: Vitamin E as an antioxidant prevents to LDL oxidation, while HDL levels in the blood can be increased. Intake of high cholesterol causes high LDL levels low High Density Lipoprotein (HDL) levels, and results the deposition of cholesterol in the blood vessels. Cholesterol depositions in the blood vessels can lead to Coronary Heart Disease (CHD). CHD is a disorder caused by a narrowing of the arteries that supply blood to the heart muscle. Purpose: The study aimed to know the correlation intake of vitamin E and cholesterol with HDL level in coronary heart disease patient at Dr. Moewardi Hospital. Method of the Research: The research used observational cross-sectional. The data of vitamin E and cholesterol intake were obtained by using a 24-hour recall during 3 days. HDL level was obtained from medical record of each patient. Pearson Product Moment correlation was used to measured if any correlation between intake of vitamin E and HDL as well as intake of cholesterol and HDL level. The sampling technique used consecutive sampling . Results: Most were male (88.6%). The subjects with vitamin E intake is not good category of 100% and the subjects who good in cholesterol were 61.4%. The subjects with abnormal HDL levels were 95.5%. The correlation result of vitamin E intake and HDL obtained p = 0.510 which means that there was no correlation between vitamin E intake and HDL levels. The test results for the cholesterol intake and HDL levels obtained p = 0.042 which means that there was correlation between cholesterol intake to HDL. Conclusion: There is correlation among intake of cholesterol to HDL levels in coronary heart disease patient at Dr. Moewardi Hospital's ward.